2019
DOI: 10.1002/mdc3.12829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deep Brain Stimulation on Postural Trunk Deformities: A Systematic Review

Abstract: Background Deep brain stimulation (DBS) effects on postural deformities are still poorly explored. Methods Systematic review in accord with the Preferred Reporting Items for Systematic review and Meta‐Analysis guidelines (PRISMA). Results All 38 studies that met predefined eligibility criteria had high risk of bias attributed to retrospective analysis of heterogeneous populations with variable and incompletely reported demographic and clinical characteristics, definitions, outcomes, DBS indications, targets, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…The follow-up results showed that GPi-DBS can significantly improve postural alignments in PD patients with camptocormia, and the correlation analysis suggests that patients with larger pre-surgical TCC/UCC angles, better levodopa responsiveness of the TCC angle and higher connectivity from VTA to right S1 cortex could possibly gain greater benefits following surgery. These findings add to and extends previously published data in the aspect of clinical effectiveness and candidate selection of GPi-DBS for the treatment of camptocormia in PD 15 , 16 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The follow-up results showed that GPi-DBS can significantly improve postural alignments in PD patients with camptocormia, and the correlation analysis suggests that patients with larger pre-surgical TCC/UCC angles, better levodopa responsiveness of the TCC angle and higher connectivity from VTA to right S1 cortex could possibly gain greater benefits following surgery. These findings add to and extends previously published data in the aspect of clinical effectiveness and candidate selection of GPi-DBS for the treatment of camptocormia in PD 15 , 16 .…”
Section: Discussionsupporting
confidence: 84%
“…According to previous systematic reviews, there was also not enough evidence to adequately compare STN and GPi as the target for parkinsonian camptocormia or any of the postural deformities, e.g., Pisa syndrome and anterocollis, particularly because of the relatively small sample sizes 9 , 15 . Although compared to STN-DBS, impressive outcome (improvement of 50–100%) was seen in patients with dystonic camptocormia after GPi-DBS, this finding may not be easily replicated in PD, as dystonic camptocormia patients were younger, had shorter disease duration, and longer camptocormia duration 15 . Studies utilizing randomized designs are now required to provide stronger evidence for optimal target selection 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The high level of satisfaction we found, even when some of our participants had developed side effects or did not have their expectations fully met, reflects findings in previous studies [12,22]. While it is well-recognized that axial motor symptoms might not respond and could even worsen after DBS [23][24][25], for our participants, the reduction of pre-operative motor symptoms of PD appears to outweigh the potential negative side effects on those areas. However, there have been reports where participants, in spite of positive clinical improvements, express dissatisfaction [26,27].…”
Section: Patients' Experiences and Attitudes With Dbssupporting
confidence: 73%
“…Further reports of surgical management of opisthotonus include deep brain stim-ulation [ 46 ] and intrathecal baclofen [ 5 , 13 , 47 ], each with clinical benefit. However, not all patients are good surgical candidates, the procedures are not without risks, both in-traoperatively and long-term, and there can be insufficient benefit from either surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of opisthotonus is multifactorial, first targeting reversible causes such as discontinuation of the offending dopamine-receptor blocking drugs that may be causing acute or tardive dystonia, and the consideration of disease-specific therapies. In most cases, no such interventions are available, and supportive measures are employed, often consisting of a tiered approach beginning with oral medications (benzodiazepines, baclofen, and anticholinergics), and in more refractory cases requiring intravenous benzodiazepines for exacerbations and/or surgical interventions such as intrathecal baclofen pump or deep brain stimulation [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%